The Influence of Family Support and Health Worker Support on Pregnant Women's Behavior in HIV Testing in Gelumbang District - Rihan Putri Rafidah; Annisa Rahmawaty; Eva Elfrida Pardede; Dina Supriyati (JURNAL KESMAS DAN GIZI (JKG), 2025)
HIV testing of pregnant women is an important step to prevent HIV transmission from mother to child.  Examination coverage in Indonesia is still low, influenced by various factors, including family support and support from health workers. This study aims to analyze the influence of family support and health workers on pregnant women's decisions to undergo HIV testing.  This research design uses descriptive analytical methods with a quantitative approach. Of the 231 respondents, only 80 respondents (34.6%) had an HIV test, while the other 151 respondents (65.4%) did not. This research proves that family support has an influence on maternal behavior in HIV testing (r=0.399, p=0.000), meaning that the higher the family support, the better the behavior of pregnant women in HIV testing. Likewise, support from health workers (r=0.096, p=0.000) means that the higher the support from health workers, the better the behavior of pregnant women in HIV testing. Further research is recommended to explore socio-economic factors and pregnant women’s perceptions of HIV screening using a mixed-method approach to gain a broader understanding